KERJASAMA INDONESIA- MALAYSIA DALAM MENANGANI PEREDARAN NARKOBA DI PERBATASAN - Ade Priangani; Kunkunrat Kunkunrat; Silvia Nurindah (Dinamika Global : Jurnal Ilmu Hubungan Internasional, 2020)
Indonesia and Malaysia have close ties especially in their land borders, making it easier to access buying and selling that occurs between communities on the border. Especially in trade to drug trafficking that occurs in border areas such as the Entikong-Sarawak region. Purchase until delivery of drugs. The circulation of drugs that enter from Malaysia is not only from the waters border, but also from land to air lines. In addition, drug traffickers not only pass through the official flight routes and ports, but drug traffickers entering from Malaysia can also take advantage of unofficial lanes on the land and water borders between Indonesia and Malaysia which have minimal security. The research of this study is to find out, explore and describe the cooperation carried out by the governments of Indonesia and Malaysia in dealing with drug trafficking on the border, especially on the Entikong and Sarawak borders, where the drug smuggling is most often deposited by couriers or which is directly taken by the dealer. By changing the form of drug packaging into a form or stored in another place, which can trick the officers at immigration. This research is expected to be useful to increase the repertoire of the development of international relations science. Furthermore, practically, this research is expected to be useful and useful for decision makers, especially the central and regional governments of the two countries, in addressing drug trafficking and trafficking that occurs on the borders of the two countries, because it will threaten the lives of the two generations. The results of this study are with the cooperation of the two governments which are always discussed in once a year in the General Border Committee forum and cooperation between the institutions of the two countries such as the National Narcotics Agency, Customs, Police and PDRM are expected to help eradicate and reduce circulation and Drug sales that occur in the border areas of the two countries, both in the sea, air, and land. There were successes after Indonesia and Malaysia collaborated in combating drug trafficking as in 2014, Kuching PDRM succeeded in capturing two Indonesian Police officers related to drugs, which in this matter coordinated the POLRI through the West Kalimantan Regional Police with Malaysian PDRM. The collaboration between Indonesia and Malaysia is considered important because the location of the two countries is very close. As well as the two countries have a long coastline, this has the potential to serve as one of the entry points for drug smuggling. Although various prevention efforts have been carried out in the eradication of drugs by the two countries by involving various parties, there are still many obstacles that become obstacles in cooperation between the two countries to be able to minimize the level of drug trafficking and trafficking that occurs in border lanes, whether it's official or unofficial border lines.